Examining the effect of STEAM Maker Instruction (SMI) on socioemotional skills aptitude in multicultural and ethnically diverse undergraduate settings - Fujun Li (Cogent Education)
This study examined the impact of STEAM Maker Instruction (SMI) on the acquisition of a third language, and the development of socioemotional skills among multi-ethnic undergraduates (n = 265). By integrating the 5E instructional model with 36 real-world business projects, this study aimed to bridge the gap between traditional multiethnic classrooms and societal expectations. Analysis of the data indicated that socioemotional skills are essential in managing students’ anxiety and aspirations, which in turn fosters their creativity and academic performance in English for Specific Purposes (ESP). The 5E model significantly improved students’ business knowledge, learning skills, and attitudes, including learning capacity, social interaction, self-regulation, open innovation, team collaboration, and creativity. Social interactions, which rely on self-regulation, self-management, and resilience, were found to be essential for fostering creativity. This study demonstrated that SMI can develop socioemotional skills through engagement with real-world business projects. It offers a pathway for multicultural classroom teaching by incorporating SMI into undergraduate curricula. Nonetheless, this study acknowledges certain limitations, such as the limited sample size and concentration in a specific academic field. Future research should explore the long-term effects of socio-emotional skills and academic outcomes beyond the classroom. This includes examining the relationships among emotional engagement, behavioral engagement, and self-efficacy in the context of career decision-making strategies.